일경일화 복륜무늬 향 춘란 ‘아리울’ - 이주현(Joohyun Lee); 권순욱(Soon-wook Kwon); 박소연(So-yeon Park); 김동용(Dong yong Kim) (Korean journal of breeding, 2015)
본 연구진은 향기와 무늬를 갖추어 기호도를 높여 수입되 는 동양란과 경쟁력을 갖춘 품종을 육성할 목적으로 중국 춘 란 ‘대부귀’와 한국춘란 SC-005를 교배하여 2012년 신품종 ‘아리울’을 육성하였다. ‘아리울’은 황색 복륜무늬와 향기가 있는 한국 춘란 신품종으로 잎의 폭이 넓고 광택이 있으며, 잎 끝에 약간의 비틀림 이 있다. 잎의 길이는 20 cm ~ 25 cm, 폭은 1.2 cm로 모본과 비슷하였다. 꽃은 옥색이며 크기는 폭이 3 cm, 길이가 2.5 cm이었다. Cymbidium goeringi of ‘Ariul’ was developed from the cross between Daebugui and SC-005 by Semangeum Bio Center in 2001. The harvested seed was germinated and cultivated. During the cultivation, an individual plant showing unique marginal stripe pattern was selected in 2006. Through continuous cultivation and checking the special patterns in the leaf, the phenotype was fixed through 2007 ~ 2008. From field cultivation in 2009, the fixed phenotype of marginal stripe pattern was confirmed. Ariul shows clear marginal stripe patterns with yellow color. The leaf color is dark green with 20 cm ~ 25 cm length. The flower of jade color has fragrance with 3 cm width and 2.5 cm length.